Brain Tissue Oxygenation and Cerebral Metabolic Patterns in Focal and Diffuse Traumatic Brain Injury - Purins, Karlis; Lewén, Anders; Hillered, Lars; Howells, Tim; Enblad, Per (Frontiers in Neurology, 2014)
Introduction Neurointensive care of traumatic brain injury (TBI) patients is currently based on intracranial pressure (ICP) and cerebral perfusion pressure (CPP) targeted protocols. There are reasons to believe that knowledge of brain tissue oxygenation (BtipO2) would add information with the potential of improving patient outcome. The aim of this study was to examine BtipO2 and cerebral metabolism using the Neurovent-PTO probe and cerebral microdialysis (MD) in TBI patients. Methods Twenty-three severe TBI patients with monitoring of physiological parameters, ICP, CPP, BtipO2 and MD for biomarkers of energy metabolism (glucose, lactate and pyruvate) and cellular distress (glutamate, glycerol) were included. Patients were grouped according to injury type (focal/diffuse) and placement of the Neurovent-PTO probe and microdialysis catheter (injured/non-injured hemisphere). Results We observed different patterns in BtipO2 and MD biomarkers in diffuse and focal injury where placement of the probe also influenced the results (ipsilateral/contralateral). In all groups, despite fairly normal levels of ICP and CPP, increased MD levels of glutamate, glycerol or the L/P ratio were observed at BtipO2 < 5 mmHg, indicating increased vulnerability of the brain at this level. Conclusions Monitoring of BtipO2 adds important information in addition to traditional ICP and CPP surveillance. Because of the different metabolic responses to very low BtipO2 in the individual patient groups we submit that brain tissue oximetry is a complementary tool rather than an alternative to MD monitoring.